Knocking down hypoxia-induced Semaphorin 6B may attenuate the progression of cervical cancer through regulating macrophage M2 polarization - Shuyan Yi; Sha Hu; Wenhan Li; Jing Cai; Liqiong Cai; Lufang Wang (Journal of Translational Medicine)
Abstract Background Cervical cancer is one of the most common malignancies in women, and its progression is closely associated with hypoxia and tumor-associated macrophages (TAMs) polarization in the tumor microenvironment (TME). The dynamic interaction between cancer cells and TAMs in the hypoxic tumor microenvironment is the key to promoting tumor progression. However, the mechanisms underlying this interaction remain unclear. Methods Macrophages were exposed to hypoxia, and next-generation sequencing was performed to analyze differentially expressed genes. TCGA data were used to identify the up-regulated genes that were independently associated with patient survival. Multiplex immunofluorescence was employed to identify semaphorin 6B (SEMA6B)-positive TAMs in human cervical cancers, and the correlation between their infiltration and clinicopathological characteristics were analyzed. TCGA, GEO, and TIMER databases were used to assess correlations between SEMA6B expression and patient survival and immune cell infiltration patterns. The SEMA6B expression in macrophages was knocked down by using siRNAs. Cell proliferation and mobility were evaluated in vitro, and flow cytometry, PCR and Western Blotting were conducted to determine the polarization of macrophages. Results After exposure to hypoxia, 236 genes were up-regulated in macrophages. Among them, SEMA6B exhibited a significant association with poor survival. In addition, abundant CD206 + SEMA6B + TAMs were associated with poor prognosis in cervical cancer patients. Database analysis revealed that SEMA6B expression was positively correlated with the infiltration of M2 macrophages and Tregs and negatively correlated with the infiltration of CD4 + and CD8 + T cells. In vitro, knocking down SEMA6B in macrophages inhibited macrophage M2 polarization and the migration ability of macrophages. Furthermore, after coculture of macrophages with SEMA6B knockdown and cervical cancer cells, the proliferation, migration and invasion of SiHa and HeLa cells was significantly reduced in vitro. Conclusions Knocking down SEMA6B may attenuate the progression of cervical cancer through regulating macrophage M2 polarization. The mechanism of action of SEMA6B on the progression of cervical cancer in vivo still needs further research. Targeting SEMA6B may be a potential immunotherapy approach for treating cervical cancer.